Analisis Kualitas Pelayanan Puskesmas Dengan Metode Servqual - Ratna Ekasari; M. Sungging Pradana; Gusti Adriansyah; M. Adhi Prasnowo; A. Fathoni Rodli; Khoirul Hidayat (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
Business Health is a fundamental right of all individuals and all citizens are entitled to health care. With growing awareness of the public about their rights in terms of health care is one of the positive indicators increasing legal awareness in society. The downside is the tendency of increasing cases of health or hospital personnel to be summoned, the patient complained of or even prosecuted legally. Puskesmas a technical unit office district/city responsible for organizing something health development in the working area. Medaeng Community Health Center is the center of the sub-sub health centers in the area of Sidoarjo. This study aims to improve the quality of health center services Medaeng in order to support government programs in the areas of health so that health community increased. This study begins with In-depth interviews were carried out on thirty patients at the time get feedback on the quality of health center services Medaeng. Then make questionnaires and distributed to one hundred patients about the attributes of services that are used in research. Attribute services used in the study is based on five dimensions of service delivery according to the method Service Quality (SERVQUAL). Five dimensions are dimensions tangibles, reliability dimension, the dimension of empathy, assurance dimension and the dimension of responsiveness. After distributing questionnaires SERVQUAL next step is to process data and perform the analysis. The calculation of the value gap is performed to determine patient satisfaction with quality attributes Medaeng services at the health center. In addition, to determine the attributes in a predetermined dimension that contributes the largest and smallest, it would require the calculation of this gap.